THE INFLUENCE OF ADDITION OF MIANA LEAF EXTRACT (Coleus scutellarioides L. Benth) IN FEED ON THE HEPATOPANCREAS OF TIGER SHRIMP (Penaeus monodon) INFECTED WITH WHITE SPOT SYNDROME VIRUS - Nurul Fadla Iftitah Jufri; Buana Basir; Muh. Imran Lapong (Journal of Fisheries and Marine Resource Management, 2026)
White Spot Syndrome Virus (WSSV) is one of the most destructive viral pathogens affecting tiger shrimp (Penaeus monodon) aquaculture, causing severe tissue damage, high mortality, and substantial economic losses. The excessive use of antibiotics and synthetic chemicals to control viral diseases has encouraged the exploration of natural immunostimulants derived from medicinal plants. This study evaluated the effect of dietary supplementation with Coleus scutellarioides L. Benth (miana) leaf extract on the clinical symptoms and hepatopancreatic histopathology of P. monodon experimentally infected with WSSV. A Completely Randomized Design consisting of four dietary treatments was employed: control (0 g kg⁻¹), 10 g kg⁻¹, 20 g kg⁻¹, and 40 g kg⁻¹ miana leaf extract. Shrimp were fed the experimental diets for 30 days prior to viral challenge. Clinical observations, histopathological examination of the hepatopancreas, and water quality measurements were subsequently performed. The results demonstrated that dietary supplementation with miana leaf extract markedly reduced the severity of WSSV clinical manifestations and preserved hepatopancreatic tissue integrity compared with the untreated control. Shrimp receiving 40 g kg⁻¹ extract exhibited only mild external symptoms, maintained normal feeding behavior, and showed active regeneration of hepatopancreatic epithelial cells with considerably fewer pathological lesions. In contrast, the control group exhibited extensive tubular degeneration, nuclear hypertrophy, intranuclear inclusion bodies, and severe tissue necrosis. Water quality remained within optimal ranges throughout the experiment, indicating that the observed responses were primarily attributable to dietary treatments. These findings demonstrate that dietary C. scutellarioides leaf extract, particularly at 40 g kg⁻¹ feed, functions as an effective natural immunostimulant capable of mitigating WSSV-induced pathological damage in tiger shrimp.